Merging and interacting wave fronts for reaction - diffusion equations - Gordon, P.V.; Vakulenko, S.A. (Archives of Mechanics, 1999)
In this paper the merging and interacting kink-type solution for general reaction diffusion equations are considered. Both the analytical and numerical investigations are presented. In particular, the existence of the complicated merging, elliptic and hyperbolic fronts in two dimensions is shown.